Carcinoma of the posterior wall of the hypopharynx: surgical treatment with larynx preservation - Başaran,Bora (2022)
Abstract Introduction: Posterior pharyngeal wall is the most rare subsite for hypopharyngeal carcinomas. Because of its rarity, there are few studies published in the literature specifically concerning posterior pharyngeal wall carcinoma. Objectives: To report our functional results in patients with the carcinoma of the posterior wall of the hypopharynx after surgical treatment by resection via a lateral or infrahyoid pharyngotomy approach, with the preservation of the larynx and reconstruction with a radial forearm free flap. Methods: The study included 10 patients who underwent surgery for a carcinoma of the posterior wall of the hypopharynx over a 6 year period. The associated postoperative morbidity was investigated and functional results were analyzed. Results: Nine patients had T3 lesions and one patient had a T2 lesion. The preferred approach to access the hypopharynx was a lateral pharyngotomy in 5 patients and lateral pharyngotomy combined with infrahyoid pharyngotomy in 5 patients with superior extension to oropharynx. The pharyngeal defects were reconstructed successfully with radial forearm free flaps. Four patients received adjuvant radiotherapy only, and 4 patients with N2b and N2c neck diseases received adjuvant chemoradiotherapy. The mean duration of hospitalization was 15.6 days (range, 10–21 days). All patients achieved oral intake in a median time of 74 days (range, 15–180). Decannulation was achieved in all patients and the median time fordecannulation was 90 (range, 21–300 days). The mean followup duration was 38.3 months (range, 10–71 months) and 8 patients survived. One patient died due to regional recurrence in the retropharyngeal lymph nodes and 1 patient died due to systemic metastasis. Conclusion: Primary surgery is still a very effective treatment modality for the carcinoma of the posterior wall of the hypopharynx and does not permanently compromise the swallowing and laryngeal functions if pharyngeal reconstruction is performed with a free flap.